«Asatz avia en un alberc d'un trobador»: representacions textuals de la trobairitz Caudairenga. - CODERCH, MARION (Scripta)
The name of the trobairitz Caudairenga appears in the account of the 18 women troubadours with no extant works who are mentioned in medieval Occitan texts. Caudairenga's figure is featured in both lyric and narrative troubadour texts alongside that of her husband, the troubadour Raimon de Miraval (active between 1180 and 1213). In these instances, she is always associated with her artistic activity and described in the most flattering terms. However, she is also rejected by her husband, who, despite the different situations described in lyric and narrative texts, always seems to take issue with the fact that she is a successful poet in her own right. This paper looks at the texts where Caudairenga's character is featured with a double aim: firstly, to elucidate which is the role of her presence in the different narratives where she appears; secondly, to identify and describe the confluence of attitudes and judgements (both positive and negative) around her figure and her identity as a trobairitz. The conclusions of this study will contribute to current knowledge about the way women troubadours were viewed by their contemporaries.